Superfood and Functional Food - An Overview of Their Processing and Utilization 2017
DOI: 10.5772/66298
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran as a Functional Food: An Overview of the Conversion of Rice Bran into a Superfood/Functional Food

Abstract: Rice bran is a byproduct of the rice milling process; it constitutes 10% of rice, with a potential global production of 48 million tons per year. The major portion of this is used as animal feed or discarded as waste material. However, rice bran is attracting attention from researchers because it is widely available, cheap and rich in nutrients such as protein, fat, carbohydrates, bioactive compounds and dietary fiber. Many foodprocessing techniques that have improved rice bran resources have been pioneered, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 61 publications
(72 reference statements)
1
24
0
Order By: Relevance
“…The unsaturated fatty acid levels were higher than the saturated ones. The main FAs identified in all samples (P. sapidus biomass, RB and FRB) were linoleic, oleic, and palmitic acids and these results are consistent with those mentioned in the literature [6][7][8]26]. In FRB, the linoleic and oleic FAs showed a small increase compared to the control substrate after six days of SSF, while the arachidic and behenic FAs disappeared after four days of fermentation, suggesting that the fungus could play a role in such (bio) transformations (Table 2).…”
Section: Effects Of the Ssf On The Fatty Acid Composition Of Rice Bransupporting
confidence: 92%
See 3 more Smart Citations
“…The unsaturated fatty acid levels were higher than the saturated ones. The main FAs identified in all samples (P. sapidus biomass, RB and FRB) were linoleic, oleic, and palmitic acids and these results are consistent with those mentioned in the literature [6][7][8]26]. In FRB, the linoleic and oleic FAs showed a small increase compared to the control substrate after six days of SSF, while the arachidic and behenic FAs disappeared after four days of fermentation, suggesting that the fungus could play a role in such (bio) transformations (Table 2).…”
Section: Effects Of the Ssf On The Fatty Acid Composition Of Rice Bransupporting
confidence: 92%
“…Several authors reported the beneficial effects of the fermented rice bran using Rhizopus oryzae or Lentinula edodes, not only in the enhancement of the nutritional quality of the final product but also its bioactivity [2,4,24]. Oil removal after fermentation could avoid various drawbacks like lipids oxidation, generation of unpleasant flavors, and loss of nutritional value [5,6,25]. Moreover, the product could be stabilized, thus extending product shelf life (e.g., feed supplement).…”
Section: Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…process, 70% rice is obtained, while rice hull (20%), rice bran (8%), and rice germ (2%) are the by-products. The major portion of this is used as animal feed or discarded as waste material [54]. However, rice bran is attracting attention from Figure 15.…”
Section: Extraction and Isolation Of Protein Form Rice Branmentioning
confidence: 99%